Dinâmica de margens em rios semiáridos: aplicações metodológicas no rio Jaguaribe – Ceará – Brasil - Andrade, José Hamilton Ribeiro (2016)
The erosion of a riverbank is a natural phenomenon, being it very dynamic and capable of being accelerated by human activities. The understanding of riverbank erosion is crucial for studies related to fluvial geomorphology, because this phenomenon causes environmental disturbances, thus it can lead to problems of social and economic order. Most of the studies on riverbanks erosion were developed in temperate regions and in small watersheds of rivers. In Brazilian territory, some work was carried out in the Paraná River basin. In semi-arid regions such as the Northeast Brazil, few studies like these were developed. In rivers located in semi-arid regions, the erosive processes are observed with greater magnitude in above average rainy seasons, which favors the occurrence of the level of full riverbanks, contributing to the widening of the canal. This is quite different from rivers located in more humid regions in which the flow and rainfall are more regular, thus the widening of the river is most common. This study aims to analyze the dynamics of riverbank erosion in the Jaguaribe River, in its lower course, precisely in Quixeré town. The Jaguaribe River is one of the main rivers of Ceará, it is a semiarid river and it has its subsidiaries controlled by dams. For that it have been selected over a stretch of 10 km of the river in nine sections which were grouped into three areas types, that is: preserved areas, partially preserved areas and degraded areas. The setbacks of the monitored riverbanks were followed monthly via the pin method. Also, some soil samples were collected to determine the root density at the riverbanks, besides the application of an Infiltration test based on Maia (2014). Satellite images from 1980 and 2014 were worked for checking the uses and land use in the study area, and to analyze the morphological changes of the river. The results showed that the volume eroded in the sections monitored was considered low, degraded areas have higher volumes eroded, comparing the conserved and partially preserved areas. For the study period (June / 2014 to May / 2015) the main factor responsible for riverbank erosion was the precipitation, even this have been below the historical average. Flow rates and the change in river levels have been not decisive for erosion during the study period. Among the uses observed in the fluvial plains, pastures and irrigated agriculture stand out, suppressing the riparian forest that acts in the stability of the riverbanks. The main erosion observed in the stretch under study has been the laminar riverbank erosion, corrosion, collapse by shearing and the collapse by tipping. With this, it was found that the ciliary vegetation contributes strongly on the stability of riverbanks, minimizing erosion. The low erosive rates are related to reduced rainfall occurred in the area and it may have very high volumes in more rainy years and with higher flow rates